DAMPAK SKEMA PERDAGANGAN GENERALISED SCHEME OF PREFERENCES (GSP) TERHADAP PERDAGANGAN KAKAO INDONESIA KE UNI EROPA (TAHUN 2009-2014) - Setyasih Harini, Florensia Garner & (Transformasi, 2015)
This research entitled "The Impact of Generalised Scheme of Preferences (GSP) TradingScheme Towards The Indonesian Cocoa Trade to The European Union (2009-2014)". Thisresearch begins from the fact that Indonesia is the world‟s third largest cocoa beans'producer. As the top cocoa beans' producer, Indonesian cocoa trade is relatively low. InEuropean Market−world‟s most potential market for cocoa−Indonesia can not compete wellwith the other countries and even those which not a cocoa beans producer. The cause is thetariff which is the provision of a Generalised Scheme of Preferences (GSP) trading scheme.GSP is an international economic policy in the field of trade by the European Union, which isintended to facilitate developing countries to have better access to enter the European marketwith tariff reduction mechanism. However, these benefits were not perceived by Indonesia.Losing in competition with other countries in the European market makes Indonesia sufferedmany losses whether in quantity as well as quality. Tariff in this scheme is a form ofprotection applied by the European Union against imported products. Although suchprotection has been reduced, Indonesia still experience significant barriers in its cocoa tradewith the European Union. Intergovernmental diplomacy needs to be done so that theIndonesian cocoa obtain better trading facilities. Thus the potential of Indonesian cocoa canbe put to good use and more leverage.Key Words : Generalised Scheme of Preferences, Trade Policy, Tariff Barriers, Protection,Indonesian-European Union‟s Cocoa Trade